Population dynamics and fisheries assessment of the bigeye thresher (Alopias superciliosus) in the Atlantic: a comparison between North Atlantic and South Atlantic stocks - Carvalho, Joana Fernandez de (2016)
Tese de doutoramento, Ciências do Mar, da Terra e do Ambiente (Biologia Pesqueira), Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015